Требования к перспективным средствам контроля и предотвращения перегрузок в телекоммуникационных сетях - Старкова, Е. В. (ХНУРЭ, 2011)
The given work is devoted to the problems of congestion control and congestion avoidance in networks. It is noted that the most common means of congestion avoidance are Active Queue Management (AQM) algorithms, implemented on the routers. AQM algorithms have been designed to be able to actively control the average queue length in routers supporting TCP traffic, and thus to be able to prevent congestion and resulting packet loss as much as possible. The basic drawbacks of these algorithms are indicated and the requirements that they must satisfy are formulated
Keywords: телекоммуникационные системы; сетевые услуги; сетевые технологии